SSR MARKERS REVEALED GENETIC DIVERGENCE OF RICE BROWN PLANTHOPPER POPULATIONS MAINTAINED ON TWO SETS OF DIFFERENTIAL HOST VARIETIES - Chaerani Chaerani; Siti Yuriyah; Ahmad Dadang; Kusumawaty Kusumanegara; Diani Damayanti; Bahagiawati Amir Husin; Sutrisno Sutrisno; Muhamad Yunus (Indonesian Journal of Agricultural Science, 2021)
Resistance screening of promising rice lines in Indonesia requires the use of brown planthopper (BPH) biotypes 1, 2, and 3. Three BPH populations have been raised as biotypes 1, 2, and 3 on differential rice host of improved varieties Pelita I-1 (no Bph gene), IR26 (Bph1), and IR42 (bph2), respectively. Three alternative populations have also been developed on the respective traditional varieties TN1 (no Bph gene), Mudgo (Bph1), and ASD7 (bph2). Although these populations displayed two virulent patterns other than biotype 1 to 3 phenotypes, they were expected to be discriminated into two virulence groups by SSR analysis. The study aimed to investigate the level of genetic variation among the six BPH populations using SSR markers and to relate it with the observed virulence patterns. Genotyping of 30 females with 29 polymorphic SSR markers revealed higher genetic parameter values in populations reared on improved varieties than those on traditional varieties. This difference was marked as two population clusters in PCoA plots corresponding to the host variety type, in contrast to the previous assumption that clustering would be based on virulence patterns. The presence of individuals with unwanted virulence allele, either resulting from contamination during the long period of rearing or lack of host adaptation period, is suspected. The result of this study indicates that the six populations are not suitable for resistance screening. Virulence selection must be performed until they attain biotype 1 to 3 phenotypes which can be genetically separated by DNA markers.